Factors That Cause Student Dropouts and Mutations to Strengthen Student Character at MAS Mifftahul Jannah Learning Space - Aisyah Nuramini; Khrisfison Khrisfison; Nelly Hastuti (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2025)
Students are vital to the continuity of education. The existence of students needs to be regulated to ensure the quality of education. One form of student regulation is dropout and transfer. This study provides a new perspective on how managing student dropouts and transfers can contribute to character building. This study aims to identify the factors causing transfers and dropouts, as well as the efforts made by schools to prevent dropouts and transfers, to strengthen student character. This study uses a qualitative approach, with a case study type of research. The research was conducted at MAS Mifftahul Jannah, Bengkalis, Bengkalis Regency. The data collection techniques were in-depth interviews and observation. The results of the study show that the factors causing student dropouts and transfers originate from the students themselves (internal factors), such as the students' inability to adapt to school rules and the unattractiveness of the school environment. Reducing student dropout and transfer rates can be achieved by strengthening character education values such as discipline, hard work, and responsibility. Strengthening these character values is expected to create moral, social, and academic resilience in students